Réponses

2014-05-11T13:00:48+02:00
 3 ( 2x – 1 ) = 2 - ( x – 3 )
6x - 3 = 2 - x + 3
6x + x  = 2 + 3 + 3
7x = 8
x= 8/7

5 – 2 ( x + 3 ) = 3 – x 
5- 2x - 6 = 3 - x 
- 2x + x = 3 - 5 + 6
- x = 4
x = - 4

8 ( x – 2 ) = 4 ( 2x – 4 ) – 3x
8x - 16 = 8x - 16 - 3x
8x - 8x + 3x = - 16 +16
3x = 0
x = 0
2014-05-11T13:00:59+02:00
Bonjour
3 ( 2x – 1 ) = 2 - ( x – 3 )
6x - 3 = 2 - x +3
6x +x = 2 +3 +3
7x = 8
x = 8/7

5 – 2 ( x + 3 ) = 3 – x
5 - 2x - 6 = 3 -x
-2x +x = -5 +6 +3
-x = 4
x = -4

8 ( x – 2 ) = 4 ( 2x – 4 ) – 3x

8x - 16 = 8x -16 -3x
8x -8x +3x = -16+16
3x = 0
x = 0